SUSANNA TAMARO: REPERE ALE ROMANULUI ANTIEDUCAŢIONAL - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2010)
The present article outlines an overview of prose by Italian writer Susanna Tamaro. The study traces the spiritual biography of the writer as it is identified in confessional texts, memoirs, essays or fiction. The author considers that there is a relationship between textual and auto-biographical typology.